An Integrated Quantitative Proteomics Workflow for Cancer Biomarker Discovery and Validation in Plasma - Kumar, Vipin; Ray, Sandipan; Ghantasala, Saicharan; Srivastava, Sanjeeva (Frontiers in Oncology, 2020)
Blood plasma is one of the most widely used samples for cancer biomarker discovery research as well as clinical investigations for diagnostic and therapeutic purposes. However, the plasma proteome is extremely complex due to its wide dynamic range of protein concentrations and the presence of high-abundance proteins. Here we have described an optimized integrated quantitative proteomics pipeline combining the label-free and multiplexed-labeling-based (Isobaric tags for relative and absolute quantitation) plasma proteome profiling methods for biomarker discovery, followed by the targeted approaches for validation of the identified potential marker proteins. In this workflow, the targeted quantitation of proteins is carried out by multiple-reaction monitoring (MRM) and parallel-reaction monitoring (PRM) mass spectrometry. Thus, our approach enables both unbiased screenings of biomarkers and their subsequent selective validation in human plasma. The overall procedure takes only ~ 2 days to complete including the time for data acquisition (excluding database searching). This protocol is quick, flexible and eliminates the need for a separate immunoassay-based validation workflow in blood cancer biomarker investigations. We anticipate that this plasma proteomics workflow will help accelerate cancer biomarker discovery program and provide a valuable resource to the cancer research community.